Foot and Ankle Related Sex-Specific Analysis Within High-Impact Journals. (March 2020) - Gianakos, Arianna L.; George, Nicole; Merklein, Meghan; Chambers, Lori; Ferkel, Richard; DiGiovanni, Christopher; Kennedy, John G.
Background: The impact of patient sex on the prevalence of foot and ankle injuries has been established. Reporting of differences on treatment outcomes is lacking. The purpose of this study was to identify trends in sex-specific outcomes across high-impact journals over a 5-year time period. Methods: Two independent investigators reviewed journal issues published during 2 calendar years (2011 and 2016) in the 5 highest-impact orthopedic foot and ankle/sports subspecialty journals ( Foot & Ankle International [ FAI ], Foot and Ankle Surgery [ FAS ], American Journal of Sports Medicine [ AJSM ], Arthroscopy, and Knee Surgery, Sports Traumatology, Arthroscopy [ KSSTA ]). Studies were stratified into those that involved sex-specific analysis (SSA), where sex was a variable in a multifactorial statistical model, and those that only reported sex as a demographic characteristic or utilized sex-matched cohorts. Results: A total of 473 studies evaluating a total of 273 128 patients met criteria. An average of 43.9% (119 967 patients) of the population were female. Only 16.7% (79/473) of studies included sex as variable in a statistical model. Thirteen percent (25/193) and 19.3% (54/280) of studies reported SSA in 2011 and 2016, respectively. FAI was the only journal demonstrating a significant improvement of reporting SSA from 2011 to 2016 ( P < .002). Thirty percent (24/79) of studies that performed SSA demonstrated significant differences between male and female outcomes. Conclusion: Reporting of SSA in the orthopedic literature continued to be lacking. Only 16.7% of all articles evaluated in 2011 and 2016 performed SSA, with 30% of this subset reporting a statistically significant difference in outcomes. Level of Evidence: Level III, comparative study.